PADUKA service : Dimension and Implementation of Population Administration - Shofy Amalia; Zahra Rahmadenia; Sri Wulandari; Farida Nurfalah (Syntax Corporation Indonesia, 2025)
PADUKA (Collective Service for Registration of Population Documents and Civil Registration in Villages) is a digital innovation from the Cirebon Regency Disdukcapil which aims to make it easier for the community to access population administration services. This service runs on a non-mandatory cooperation agreement between the Disdukcapil and the village, so that the services are not evenly distributed in Cirebon Regency. This research aims to determine the dimensions and implementation of PADUKA's services, and identify obstacles and efforts to improve the quality of services. The methods used in the study are qualitative methods, data collection through observation, interviews, and dookumentation, with analysis based on the E-Govqual theory according to Papadomichelaki and Mentaz (2012) which includes six dimensions. Based on the results of the research, the implementation of PADUKA services provides convenience in the population administration process based on the quality standards of Content and Appearance that runs optimally. Meanwhile, the dimensions of Ease of Use, Trust, Reliability, Citizen Support, Functionality of Interaction are still constrained in implementation. The main obstacle lies in the nature of non-mandatory and permanent cooperation agreements, as well as communication and low quality of human resource competencies. The efforts made are to improve the cooperation agreement period, operator training, and system improvement. Overall, PADUKA has shown a positive contribution to the transformation of digital-based public services, although more intense evaluation is needed to ensure equitable distribution and optimization of services.